2018
DOI: 10.3390/rs10040532
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Airborne LiDAR and Optical Data to Estimate Forest Aboveground Biomass in Arid and Semi-Arid Regions of China

Abstract: Forest Aboveground Biomass (AGB) is a key parameter for assessing forest productivity and global carbon content. In previous studies, AGB has been estimated using various prediction methods and types of remote sensing data. Increasingly, there is a trend towards integrating various data sources such as Light Detection and Ranging (LiDAR) and optical data. In this study, we constructed and compared the accuracies of five models for estimating AGB of forests in the upper Heihe River Basin in Northwest China. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 77 publications
1
32
0
Order By: Relevance
“…Among the three nonparametric algorithms in this study, GPs generated suboptimal predicted results in terms of R 2 , RMSE, and relative error. The SVM showed the least favorable accuracy, which is consistent with the conclusions from recent studies [59,60].…”
Section: Discussionsupporting
confidence: 92%
“…Among the three nonparametric algorithms in this study, GPs generated suboptimal predicted results in terms of R 2 , RMSE, and relative error. The SVM showed the least favorable accuracy, which is consistent with the conclusions from recent studies [59,60].…”
Section: Discussionsupporting
confidence: 92%
“…The evaluation of the forest AGB mapping results by the four models was insufficient for this study as we were limited by the sample size. Future verification work should be conducted; this is conventionally done by independent sample sets or by acknowledged high-accuracy results such as airborne data, especially unmanned aerial vehicle LiDAR data [17,97].…”
Section: Mapping Of Four Agb Modelsmentioning
confidence: 99%
“…Similarly, previous researchers have used these four methods to estimate forest AGB and achieve good accuracies, while results of the models' comparison vary compared with this study. Cao et al (2018), integrating airborne LiDAR and optical data, compared the accuracies of forest AGB models in the upper Heihe River Basin in northwest China, and found that RF was the best (R 2 = 0.9, RMSE = 13.4 Mg·ha −1 ), following by ANN and SVR [17]. Based on Landsat satellite imagery, Wu et al (2016) implemented the optimal spatial forest AGB estimation in northwestern Zhejiang Province, China, and RF (R 2 = 0.6, RMSE = 26.4 Mg·ha −1 ) also performed better than SVR [11].…”
Section: The Comparison Of Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It works with UAV platforms and provides accurate three-dimensional structural information of the vegetation canopy (Wallace et al 2014). It provides rapid and nondestructive estimates of structural information, such as height, volume, leaf area index, and leaf area density of vegetation, which can resolve the problem of spectral saturation that occurs in optical remote sensing (Cao et al 2018;Du et al 2016;Luo et al 2018;Tagarakis et al 2018). Unlike manned aircraft, UAVs are being increasingly used to provide detailed, high-resolution imagery and associated digital elevation models (DEMs) for surface processes and geomorphological research (James & Robson 2014).…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%